Role of Intravenous Immunoglobulin (IVIG) in Patients with Guillain Barre Syndrome with Severe Community Pneumonia in The Intensive Care Unit (ICU) - Giovanni, Cindy; Sitio, Nurita Dian Kestriani Saragi (Journal of Society Medicine, 2024)
Guillain-Barré syndrome (GBS) is an acute flaccid polyneuropathic disease that occurs after infection and is caused by an immune system response. GBS patients often experience acute respiratory distress that requires mechanical ventilation. Nerve impairment in GBS can lead to various problems such as difficulty breathing, ineffective coughing, and difficulty swallowing, increasing the risk of lung infection. Community acquired pneumonia (CAP) is a lung infection acquired outside the hospital. The severity of CAP is directly proportional to the mortality rate. Appropriate antibiotic therapy can reduce the duration of treatment and mortality in CAP. The case report involves a 50-year-old man with GBS and CAP who required treatment in the Intensive Care Unit (ICU). The management of GBS included the use of mechanical ventilation, antibiotics, and intravenous immunoglobulin (IVIG), resulting in improvement after 19 days, with the patient eventually being discharged from mechanical ventilation. It is necessary to describe the management of GBS and CAP cases so that further management can be better and in accordance with existing literature.